Eylül Sonrasi Dinleri Öğretme-Öğrenme İslami Örneklerin Bir Ön Değerlendirmesi (Teaching-Learning Religions after 9/11: A Preliminary Assessment of Islamic Cases) - Thoha, Anis Malik (2010)
Tragedy of 9/11 has a far-reaching effect. It has changed systematically all aspects of the modern world history, especially the aspects pertaining to religions. Islam, in particular, has been the most badly affected and maligned among these religions as being projected widely the main agent behind the tragedy. Then, all negative attributes and stigmas, such as violence, terrorism, hatred, intolerance, etc., are labeled loosely and massively against Islam. Hence, the demand for reforming and restructuring the Islamic educational curricular at all levels, as well as for scrutinizing the reading materials or books required for the process of teaching-learning Islam, especially in madrasahs in the Muslim countries. Therefore, this paper is an academic attempt to assess the extent to which the tragedy has affected the process of teaching-learning Islam, and to evaluate this impact in the context of both philosophy of education, human rights, civil society and globalization.